2004
DOI: 10.1016/j.ymthe.2004.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Systemic but not intraocular Epo Gene Transfer Protects the Retina from Light-and Genetic-Induced Degeneration

Abstract: Molecules with neurotrophic activity are being evaluated for treatment of retinitis pigmentosa in animal models. In particular, great interest has been focused recently on erythropoietin (Epo). Evidence of its neurotrophic activity comes mainly from data demonstrating photoreceptor protection in a rodent light-damage model through systemic administration of a recombinant form of this hormone. Our goal was to test whether Epo retinal gene transfer can rescue or delay photoreceptor cell death. We delivered adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 43 publications
3
84
0
Order By: Relevance
“…Activation of HIF under hyperoxic conditions caused an upregulation of proangiogenic molecules Epo and VEGF that likely prevent vascular loss, ischemia, and subsequent proliferative retinopathy. Previous studies have demonstrated a deficiency of Epo during phase I of retinopathy and a protective effect in terms of vascular and neuronal survival after Epo supplementation early in phase I of the disease (16) or in other models of oxygen-induced retinal degeneration (17). Under normal O 2 tension, HIF-␣ subunits are rapidly degraded via PHD-dependent interactions with the von Hippel-Lindau protein, which is a component of the E3 ubiquitin ligase complex, resulting in degradation of the complex (10).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of HIF under hyperoxic conditions caused an upregulation of proangiogenic molecules Epo and VEGF that likely prevent vascular loss, ischemia, and subsequent proliferative retinopathy. Previous studies have demonstrated a deficiency of Epo during phase I of retinopathy and a protective effect in terms of vascular and neuronal survival after Epo supplementation early in phase I of the disease (16) or in other models of oxygen-induced retinal degeneration (17). Under normal O 2 tension, HIF-␣ subunits are rapidly degraded via PHD-dependent interactions with the von Hippel-Lindau protein, which is a component of the E3 ubiquitin ligase complex, resulting in degradation of the complex (10).…”
Section: Discussionmentioning
confidence: 99%
“…Several distinguished investigations addressed the properties of the EPO to mediate protection against retinal damage through anti-apoptotic, 29,30 anti-oxidant, 22 and antiinflammatory 26,31 actions in hypoxia-, light-, and geneticinduced models. 5,8,12,15 Furthermore, Chung et al 20 reported on his finding for the expression of EPO and Figure 2 The role of erythropoietin in eye development via anti-apoptotic action. Binding of EPO/EPOR induces JAK2 phosphorylation, dimerization, and subsequently, activation of several tyrosine residues forming docking site for STAT, NF-κB, PI3-K/Akt, and MAPK.…”
Section: The Role Of Epo In the Eyementioning
confidence: 94%
“…2,13,14,98,99 Based on the positive pre-clinical outcomes with various animal models, 5,8,12,15 EPO may offer a promising future therapy for treatment of many common ocular disorders plaguing us today such as DR, retinal detachment, glaucoma, retinopathy of prematurity, AMD, and optic neuritis. Current clinical trials are using established recombinant EPO such as epoietin alfa 100,101 and darbepoietin, 100,102 which do not specifically target to correct nerve circuitry activity in the eye.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 An increasing number of studies have demonstrated the neuroprotective effects of EPO and its receptor, by anti-apoptotic mechanisms. Several studies have indicated that EPO can protect photoreceptor cells from the effects of lightinduced and hereditary retinal dystrophy; [2][3][4][5] protect retinal neurons from ischemiareperfusion injury, 6 and retinal ganglion cells after acute and chronic ocular hypertension; [7][8][9] promote ganglion cell survival and axonal regeneration after optic nerve transection; [10][11][12] attenuate inflammation in multiple sclerosis optic neuritis; 13,14 reduce the permeability of the retinal barrier and protect retinal neurons in diabetic retinopathy; [15][16][17][18] relieve diabetic macular edema; 19 enhance the stability of hypoxic retinal vessels; 20,21 and has a neuroprotective role in pigment epithelial cells subjected to photo-oxidative damage. 22 EPO exerts its biological effects through interaction with EPO receptor (EPOR).…”
Section: Introductionmentioning
confidence: 99%